Exercise training modifies the bone and endocrine response to graded reductions in energy availability in skeletally mature female rodents - Bloomfield, Susan A.; Swift, Sibyl N.; Metzger, Corinne E.; Baek, Kyunghwa; De Souza, Mary Jane; Lenfest, Scott; Shirazi-Fard, Yasaman; Hogan, Harry A. (Frontiers in Endocrinology, 2023)
Reductions in energy availability leading to weight loss can induce loss of bone and impact important endocrine regulators of bone integrity. We sought to elucidate whether endurance exercise (EX) can mitigate bone loss observed in sedentary (SED) skeletally mature rodents subjected to graded energy deficits. Female virgin rats (n=84, 5-mo-old; 12/group) were randomized to baseline controls and either sedentary (SED) or exercise (EX) conditions, and within each exercise status to adlib-fed (ADLIB), or moderate (MOD) or severe (SEV) energy restriction diets for 12 weeks. Rats assigned to EX groups performed treadmill running to increase weekly energy expenditure by 10%. MOD-ER-SED, SEV-ER-SED, MOD-ER-EX and SEV-ER-EX were fed modified AIN93M diets with 20%, 40% 10%, and 30% less energy content, respectively, with 100% of all other nutrients provided. Energy availability (EA) was effectively reduced by ~14% and ~30% in the MOD-ER and SEV-ER groups, respectively. MOD-ER for 12 weeks resulted in few negative impacts on bone and, except for serum leptin in MOD-ER-SED rats, no significant changes in endocrine factors. By contrast, SEV-ER in SED rats resulted in significantly lower total body and femoral neck bone mass, and reduced serum estradiol, IGF-1 and leptin. EX rats experiencing the same reduction in energy availability as SEV-ER-SED exhibited higher total body mass, lean mass, total BMC, and higher serum IGF-1 at the end of 12 weeks. Bone mechanical properties at 3 bone sites (mid-femur, distal femur, femoral neck) were minimally impacted by ER but positively affected by EX. These findings indicate that combining increased EX energy expenditure with smaller reductions in energy intake to achieve a targeted reduction in EA provides some protection against loss of bone mass and lean mass in skeletally mature female rats, likely due to better preservation of circulating IGF-1, and that bone mechanical integrity is not significantly degraded with either moderate or severe reduced EA.